Environment behavior models for scenario generation and testing automation. - Auguston, Mikhail
This paper suggests an approach to automatic scenario generation from environment models for testing of real-time reactive systems. The behavior of the system is defined as a set of events (event trace) with two basic relations: precedence and inclusion. The attributed event grammar (AEG) specifies possible event traces and provides a uniform approach for automatically generating, executing, and analyzing test cases. The environment model includes a description of hazardous states in which the system may arrive and makes it possible to gather statistics for system safety assessment. The approach is supported by a generator that creates test cases from the AEG models. We demonstrate the approach with case studies of prototypes for the safety-critical computer-assisted resuscitation algorithm (CARA) software for a casualty intravenous fluid infusion pump and the Paderborn Shuttle System.
Keywords: Software; Software engineering; Testing and debugging; Design; Reliability; Model-based testing; Reactive and real time system testing; Testing automation